Physiological Effects of Wearing N95 Respirator on Medical Staff During Prolong Work Hours in Covid-19 Departments. Issue 6 (4th June 2022) - Shechtman, Liran; ben-Haim, Gal; Ben-Zvi, Ilan; Steel, Laurence; Ironi, Avinoah; Huszti, Ella; Chatterji, Sumit; Levy, Liran
Abstract : Although the protective effect of N95 respirators is well defined, the potential physiologic impacts of wearing respirator during long work shifts remains undetermined. According to the results of our study, prolonged wearing of N95 respirator by healthcare professionals is associated with physiological effects on gas exchange. Cardio-respiratory variables remained unaffected. Abstract : Objective: The objective of the current study was to determine gas exchange abnormalities and physiological changes among healthcare workers during a 4-hour emergency department (ED) shift while wearing the N95 respirator. Methods: Single-center prospective observational study. Comparisons of paired measurements were performed using a non-parametric Wilcoxon matched-pairs signed-rank test. Results: Forty-one subjects were included. Prolonged N95 respirator use was associated with a significant decline in plasma pH (7.35 mmHg vs 7.34 mmHg, P = 0.02), PvO2 (23.2 mmHg vs 18.6 mmHg, P < 0.001) and a concurrent increase in EtCO2 (32.5 mmHg vs 38.5 mmHg, P < 0.0001). PvCO2 and bicarbonate levels did not differ. No significant change was observed for heart rate or oxygen saturation. Conclusion: Using an N95 respirator for prolonged periods by healthcare professionals may provoke changes in gas exchange. The clinical significance of these changes remains to be determined.